1970
DOI: 10.1210/endo-87-5-900
|View full text |Cite
|
Sign up to set email alerts
|

In VitroMetabolic Effects of Bovine Growth Hormone Fragments in Adipose Tissue

Abstract: A limited tryptic digest of bovine growth hormone, which dissociated in 50 % acetic acid into 2 fragments of 16,000 and 5000 molecular weight, was evaluated for bovine growth hormone (BGH) activity in rat adipose tissue in vitro. Both fragments, whether tested individually or as mixtures in equimolar ratio, possessed the several in vitro metabolic activities commonly associated with native BGH: ( 14 C)-glucose uptake, its oxidation to CO2 and incorporation into glyceride-glycerol, glycerol release, and ( U C)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1974
1974
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…As also described for FDC-P1 cells transfected with a hybrid of the hGHR extracellular domain linked to the murine granulocyte/macrophage-CSF receptor transmembrane and intracellular domains (16), hGH120R cannot induce Ba/F3(8/6) or IM9 cell proliferation (34,36). This was originally attributed to nonformation of the "active" hGH⅐(hGHR) 2 complex, but recent data show that hGHG120R dimerizes and internalizes the GHR as well as does GH (37). GHR05 binding does not increase in Ba/F3(8/6) cells incubated with hGHG120R, in contrast to its behavior with native hGH.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…As also described for FDC-P1 cells transfected with a hybrid of the hGHR extracellular domain linked to the murine granulocyte/macrophage-CSF receptor transmembrane and intracellular domains (16), hGH120R cannot induce Ba/F3(8/6) or IM9 cell proliferation (34,36). This was originally attributed to nonformation of the "active" hGH⅐(hGHR) 2 complex, but recent data show that hGHG120R dimerizes and internalizes the GHR as well as does GH (37). GHR05 binding does not increase in Ba/F3(8/6) cells incubated with hGHG120R, in contrast to its behavior with native hGH.…”
Section: Discussionmentioning
confidence: 94%
“…To analyze the possible relationship between the GHR05 binding increase and hGH-induced receptor conformational change, an hGH mutant (hGHG120R) was employed that is able to bind the hGHR but not to form the active hGH⅐(hGHR) 2 complex. hGHG120R has a Gly 120 3 Arg mutation affecting the second GH binding site, which impedes correct receptor dimerization and subsequent proliferation induction (33).…”
Section: Fig 4 Effect Of Hgh and Ghr05 On Cell Cycle Distribution Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the segment 96-133 of bGH represents the amino acid sequence requisite for growth hormone activity. 2,5,8) Physico-chemical properties of A-II have been investigated by circular dichroism and fluorescence emission spectroscopy.8-10) Gel filtration analyses and difference spectrum measurements revealed that a tyrosine residue in A-II was exposed on the surface of the fragment molecule existing in the monomer form and was held between the fragment molecules under the conditions where A-II existed as dimer and trimer. 11) To further elucidate the structure-function relationship of bGH in the present study, confonnations of A-II and its parent molecule, bGH, were t This work was supported in part by grants for scientific research from the Ministry of Education, Science and Culture of Japan.…”
Section: Received June 13 1979mentioning
confidence: 99%